Synthesis of Some Isoindole-1,3-(2H)-dione, Amino-oxy and Biguanidino-oxy Derivatives of Carbazole - Kumar Baregama, Lalit; Mehta , Deepika; Talesara, G.L. (Asian Journal of Chemistry, 2010)
2-(Bromoalkoxy)-1H-isoindole-1, 3-(2H)-dione are condensed with carbazole and its derivatives to give ω-N-(carbazol-5-yl) alkoxy 1K-isoindole- 1,3-(2H)-diones. Gabriels hydrolysis under acidic conditions give the corresponding amino-oxy salts. Condensation of amino-oxy salts with various para-substituted dicyandiarnide give corresponding biguanidino-oxy compounds;